Development of Paddy Yield Gap Between Java and Outside Java: Does It Have a Contribution to Paddy Yield Improvement from 2018 to 2021? - Kadir Ruslan; Octavia Rizky Prasetyo (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Increasing the paddy yield is crucial for Indonesia to maintain its national rice sufficiency amid the consistent depletion of wetland paddy areas. In this regard, the yield disparities between regions are challenging, particularly between Java and outside Java. Our study aims to examine the development of the paddy yield gap between the two regions from 2018 to 2021 and its contribution to paddy yield improvement during the period. Using the results of the National Crop-cutting Survey, we found that while the paddy yield in Java outperformed the paddy yield outside Java, the yield difference between the two regions narrowed from around 26 per cent in 2018 to 22 per cent in 2021 due to the increase of the yield outside Java. The results of the Blinder-Oaxaca decomposition suggested that the narrowing gap has a significant contribution to the national paddy yield increase from 2018 to 2021. Our finding confirms that narrowing the yield gap between the two regions by increasing the yield outside Java is crucial to improving paddy yield in Indonesia. Our study also pointed out that improvement in irrigation systems, fertilizer use, and fertilizer assistance are important factors in maintaining the paddy yield and narrowing the gap.